2023
DOI: 10.3390/ijms24065527
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Extracellular Vesicles microRNAs Are Altered in Women Undergoing Preterm Birth

Abstract: Preterm labor (PTL) and preterm premature rupture of membranes (PPROM) lead to high perinatal morbidity/mortality rates worldwide. Small extracellular vesicles (sEV) act in cell communication and contain microRNAs that may contribute to the pathogenesis of these complications. We aimed to compare the expression, in sEV from peripheral blood, of miRNAs between term and preterm pregnancies. This cross-sectional study included women who underwent PTL, PPROM, and term pregnancies, examined at the Botucatu Medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Ramos et al investigated miRNA expression in small extracellular vesicles (sEV) from peripheral blood, comparing term and preterm pregnancies. The study identified differential expression of miR-612 and other miRNAs associated with cellular senescence in preterm pregnancies, highlighting miRNAs' potential role in preterm labor and premature rupture of membranes [35].…”
Section: Resultsmentioning
confidence: 95%
“…Ramos et al investigated miRNA expression in small extracellular vesicles (sEV) from peripheral blood, comparing term and preterm pregnancies. The study identified differential expression of miR-612 and other miRNAs associated with cellular senescence in preterm pregnancies, highlighting miRNAs' potential role in preterm labor and premature rupture of membranes [35].…”
Section: Resultsmentioning
confidence: 95%
“…This is not surprising, as miRNAs in prenatal plasma and miRNAs in postpartum human milk are thought to have different tissue sources, with the placenta being a major source of circulating miRNA during pregnancy and the mammary epithelium being the main source of miRNA in human milk [3][4][5]. Of these shared, ubiquitously expressed EVP miRNAs, several have important roles in immune function or have been implicated in pregnancy complications (e.g., hsa-miR-302d-3p, hsa-miR-320e, hsa-miR-1253, hsa-miR-378e, has-miR-1253) [34][35][36][37]. These common miRNAs may, therefore, serve important regulatory purposes for child development and growth across these two windows.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated serum BEV IgG antibody-based asthma and chronic obstructive pulmonary disease diagnosis have also been tested [137] . Additionally, metagenomic and metabolomic profiling of stool BEVs revealed significantly altered Firmicutes and Proteobacteria as well as amino acids, carboxylic acids, and short-chain to long-chain fatty acids metabolism in colorectal cancer patients [305] . Similarly, human EVs and BEVs found in placental tissues can facilitate the identification of new preeclampsia or preterm birth-associated inflammatory biomarker targets.…”
Section: Stimulation Of Preeclampsia Preterm Labor and Birthmentioning
confidence: 97%